Analisis Strategi Bisnis untuk Meningkatkan Penjualan Menggunakan Analisis SWOT di PT. BM - Dwi Yanti, Fisma; Ainun Nisah, Firda (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
In the increasingly fierce business world competition, marketing products to meet industry needs requires companies to find fast and appropriate strategies. A strategy is needed to be able to overcome competition and seize market share. Therefore, this study aims to identify internal and external factors of the company to find strategies in product development. This research uses quantitative descriptive research methods by describing the situation and explaining the situation based on facts and existing data. SWOT analysis is an analytical method used with external factor analysis methods and internal company factor analysis. The results of the analysis at PT.BM is placing the Strength>Opportunity strategy, Opportunity>Weakness Strategy, Strength>Threat Strategy, and Threat>Weakness Strategy. This condition explains that PT. BM is in a position to utilize the SO strategy which has the highest score value of = 2.31. Furthermore, followed by the strategy ST = 2.31, WO = 1.79, and WT = 1.61 with this analysis, it is expected that the company can continue to improve product quality, develop product innovations with unique designs, it is hoped that the company can add and prepare a professional workforce, improve services, and promotions massively. Through the strategic plan obtained from the results of the analysis, it is expected to help the development of the company for the better. Keywords: EFAS, IFAS, SWOT Analysis